Determination a Reasonable Concession Period for (PPP) Projects - Ali Hasan Hadi; Kadhim Raheim Erzaij (Salehan Institute of Higher Education, 2019)
Public Private Partnership (PPP) are agreements where public bodies enter into long term contractual with private entities for construction or management the public sector facilities, or provision services to the community. Internal rate of return (IRR), pay back regime or tariff, and the concession period (CP) are essential items to success (PPP) projects. This research presents a systematic approach for a win-win partnership contract determined on a quantitative basis, by informing the partnership parties how long contract period should be made. Essence of the proposed methodology is that project completion time should allow a competent contractor to complete the project on schedule and operation period should be long enough to enable the concessionaire to achieve a reasonable return, but not too long such that concessionaire’s return is excessive and public sector’s interests are sacrificed. A case study of a PPP project in Mayoralty of Baghdad was conducted to evaluate performance of the developed mathematical models. The determined concession period (CP) has found to be approximately equal to actual concession period (CP) granted to the private sector. Evaluation shows the possibility to adopt the proposed approach to determine the concession period (CP) more effectively. Instead of opportunism policy, the proposed methodology enables local government of Baghdad province to enhance its policies of awarding the partnership projects to increase private sector participation in infrastructure development. Finally, the proposed method can be used by investment practitioners as a decision support tool for contract concession period (CP), and is worth popularizing to design the contracted concession period (CCP) for partnership projects in Iraq, and also can use as a methodology to assess the critical aspects which related to partnership projects in general.